2020
DOI: 10.1186/s12891-020-03235-z
|View full text |Cite
|
Sign up to set email alerts
|

Low adherence to exercise may have influenced the proportion of OMERACT-OARSI responders in an integrated osteoarthritis care model: secondary analyses from a cluster-randomised stepped-wedge trial

Abstract: Background: To address the well-documented gap between hip and knee osteoarthritis (OA) treatment recommendations and current clinical practice, a structured model for integrated OA care was developed and evaluated in a stepped-wedge cluster-randomised controlled trial. The current study used secondary outcomes to evaluate clinically important response to treatment through the Outcome Measures in Rheumatology Clinical Trials clinical responder criteria (OMERACT-OARSI responder criteria) after 3 and 6 months be… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…This lack of further improvement may relate to inadequate exercise progression, including suboptimal intensities, during this unsupervised phase. Although it is presumed that there is a relationship between exercise adherence and outcomes in knee OA, surprisingly, the nature of the relationship is unclear given the limited research and contradictory findings [ 6 , 48 - 50 ]. For example, some studies using self-report adherence measures have found that greater adherence is linked with better pain and function outcomes [ 6 , 48 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This lack of further improvement may relate to inadequate exercise progression, including suboptimal intensities, during this unsupervised phase. Although it is presumed that there is a relationship between exercise adherence and outcomes in knee OA, surprisingly, the nature of the relationship is unclear given the limited research and contradictory findings [ 6 , 48 - 50 ]. For example, some studies using self-report adherence measures have found that greater adherence is linked with better pain and function outcomes [ 6 , 48 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although it is presumed that there is a relationship between exercise adherence and outcomes in knee OA, surprisingly, the nature of the relationship is unclear given the limited research and contradictory findings [ 6 , 48 - 50 ]. For example, some studies using self-report adherence measures have found that greater adherence is linked with better pain and function outcomes [ 6 , 48 , 50 ]. In contrast, a study using concealed accelerometers to accurately assess adherence to a 12-week home strengthening program showed no evidence of an association [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, there is strong evidence that physical therapy represented by regular exercise can be beneficial for OA. However, inconsistent results are usually obtained by different exercise models and different research groups, mainly because of that most patients cannot strictly follow the requirements of physical therapies (Moseng et al, 2020). The low exercise adherence rate is one of the reasons why exercise therapy does not respond well in some cases (Østerås et al, 2019).…”
Section: Patient Educationmentioning
confidence: 99%
“…The of OMERACT-OARSI responders in previous research of OA management varies widely. The proportion of responders varies from 25% to 83%, [36][37][38] hence, a conservative estimate in our trial would be 50% being classified as responders. No direct comparison of our study to other trials is to our knowledge available, increasing difficulty of specifying a non-inferior margin.…”
Section: Sample Size Calculationmentioning
confidence: 99%